(Table 1) Current ripples from the trench outer slope, ODP Hole 131-808C - Pickering, Kevin T; Underwood, Michael B; Taira, Asahiko (Supplement to: Pickering, KT et al. (1993): Open-ocean to trench turbidity-current flow in the Nankai Trough: flow collapse and flow reflection. In: Hill, IA; Taira, A; Firth, JV; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 131, 35-43, https://doi.org/10.2973/odp.proc.sr.131.104.1993, 1993)
The Ocean Drilling Program Leg 131, which drilled in the Nankai Trough in the western Pacific Ocean, has shown for the first time that turbidity currents are deflected and reflected against the trench slopes, such that in the trench outer slope there is a predominant pattern of currents, carrying terrigenous sediments, apparently coming from the open-ocean Shikoku Basin directly toward the trench landward-slope. The purpose of this paper is to summarize the evidence for flow rebound at ODP Leg 131 Site 808, and to show that these results have important implications for the interpretation of paleocurrents in ancient linear turbidite systems.